IBPSA Project 1: BIM/GIS and Modelica framework for building and community energy system design and operation – ongoing developments, lessons learned and challenges. (August 2019) - Wetter, M; van Treeck, C; Helsen, L; Maccarini, A; Saelens, D; Robinson, D; Schweiger, G
Abstract: IBPSA Project 1 develops and demonstrates an open-source BIM/GIS and Modelica Framework for building and community energy system design and operation. The project builds further on the completed project IEA EBC Annex 60 "New generation computational tools for building and community energy systems based on the Modelica and Functional Mockup Interface standards." This paper describes the motivation and approach of the project, and it provides an update about recent activities. These activities include development of a core Modelica library for building and community energy systems; development of BOPTEST, a virtual test bed to test advanced controllers such as MPC; development of GIS/BIM data model translators for Modelica; development of new workflows for improved productivity and quality assurance of urban-scale energy simulation; and development of DESTEST, a validation test for district energy models.